Impact of individual early life traits in larval dispersal: A multispecies approach using backtracking models. (March 2021) - Torrado, Héctor; Mourre, Baptiste; Raventos, Núria; Carreras, Carlos; Tintoré, Joaquín; Pascual, Marta; Macpherson, Enrique
Abstract: Dispersal is a key process shaping species population structure. In demersal marine fishes, which usually have sedentary adult phases, dispersion relies on drifting larval stages. However, the dynamics and seasonal variability of seawater masses can greatly determine the connectivity patterns of these species along the same geographic gradient. For this reason, detailed information on the release moment of larvae is needed to obtain accurate patterns of connectivity. In this study, we performed backtracking Lagrangian particle dispersion simulations, with individual-based early life traits data, obtained from otolith reading for 1413 juveniles of nine fish species belonging to three families (Sparidae, Pomacentridae and Labridae). For each species, individuals had been sampled from four to seven localities in the western Mediterranean Sea between the Gulf of Lion to the Gibraltar Strait. These nine species reproduce in different seasons of the year and their pelagic larval duration (PLD) range from 7 to 43 days. We identified three hydrodynamic units separated by oceanographic discontinuities (Balearic Sea, West Algerian Basin and Alboran Sea) with low settler's exchange according to our simulations, independently of the PLD and reproductive season of the species. Hatching date and PLD showed significant effects on larval dispersal distance and orientation, both at the intraspecific and interspecific levels, highlighting the importance of these variables in determining the geographic origin of individuals. Our multispecies modelling approach adds a step forward for an accurate description of larval dispersion and recruitment, key to understand population resilience and define management strategies.